2014
DOI: 10.1111/ene.12477
|View full text |Cite
|
Sign up to set email alerts
|

A study on the association between infectious burden and Alzheimer's disease

Abstract: IB consisting of CMV, HSV-1, B. burgdorferi, C. pneumoniae and H. pylori is associated with AD. This study supports the role of infection/inflammation in the etiopathogenesis of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
174
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(181 citation statements)
references
References 37 publications
4
174
2
1
Order By: Relevance
“…Recently, an animal study revealed that infection with respiratory pathogen Bordetella pertussis led to increased glial activation and Ab deposition in brain (McManus et al 2014), indicating that respiratory infection and inflammation contribute to AD pathology. Our previous study also showed that common infections and inflammation were associated with increased serum Ab levels (Bu et al 2014). Serum PCT has been used as a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an animal study revealed that infection with respiratory pathogen Bordetella pertussis led to increased glial activation and Ab deposition in brain (McManus et al 2014), indicating that respiratory infection and inflammation contribute to AD pathology. Our previous study also showed that common infections and inflammation were associated with increased serum Ab levels (Bu et al 2014). Serum PCT has been used as a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…e1a, there was a higher percentage of PD patients in the five-six seropositivities category (35% vs. 15%), a lower percentage in both the zero-two (61% vs. 74%) and three-four (4% vs. 11%) seropositivities than normal controls (P < 0.001). IB next was classified into viral burden and bacterial burden according to the previously published studies [11,16]. As only a few subjects had zero (11.8%) or three (4.4%) seropositivities toward B. burgodorferi, C. pneumoniae and H. pylori, bacterial burden was divided into two categories (zero-one and two-three).…”
Section: Exposure To Infectious Pathogens In Normal Controls and Pd Pmentioning
confidence: 99%
“…Although the exact etiology remains unknown, to date, pathogenic infection is increasingly recognized as a possible risk factor for PD [5e8]. Infectious burden (IB), defined as a composite serological measure of exposure to common pathogens such as cytomegalovirus (CMV), herpes simplex virus type 1 (HSV-1), Chlamydophila pneumonia (C. pneumonia), Borrelia burgdorferi (B. burgdorferi) and helicobacter pylori (H. pylori), has been reported to be associated with cardiovascular disease [9], stroke [10] and Alzheimer's disease [11]. Whether a causal link exists between accumulated infections and PD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the innate immune system [117][118] and pathogen responses [119] are related to Aβ imbalances, and Aβ can act as a pro-inflammatory agent in such cases [120]. The recently identified roles of infections in elevating AD risk show that inflammatory trauma plays a major role in AD pathology [121] [9]. The protective A2T mutation [125] has been widely used as a showcase of the amyloid hypothesis [101], and its lower produced A levels fit well to quantitative gain of function as the protective alternative to the Swedish mutation and A2V [126].…”
Section: Ten Challenges Of the Amyloid Hypothesismentioning
confidence: 99%